Kajian Pengelolaan Sumber Daya Air Permukaan Berbasis Geographics Information System (GIS) di Kota Bandar Lampung - Iskhaq, Firdaus bin; Purwadi, Ofik Taufik; Perangin angin, Geleng (Universitas Lampung, 2016)
Bad water resource management caused water availability unable to be fulfiled to the maximum level throughout the year, especially in the dry season. The water crisis becomes a difficult problem because the tendency of people’s anticipation only glued to the conventional water sources which are susceptible to dry out, such as wells and others. This study aimed to determine the condition of surface runoff resources in the Bandar Lampung city. And also to provide a solution of problems that often occur in the Bandar Lampung city, especially in the dry season. This research conducted using MWGIS software as a program for making geographical information of Bandar Lampung city conditions in general and rivers condition specifically. In this digital era, information of rivers based on digital data are required for society and the government as an instrument to establish decisions and policies in the management of surface runoff resources, especially in case of rivers in Bandar Lampung city. The output from MWGIS is an illustration of a geographical condition of Bandar Lampung city which in simple form map contains a variety of information that related to the geographical conditions, such as land cover data, topography, slopes, rivers, districts, villages and many others depend on how far the manufacturing database / information in MWGIS required.